Optimization of culture conditions for and assessment of kimchi-originated lactic acid bacterial isolates toward their extracellular GABA-producing ability - Lee, Jin-Sung; Kim, Keun-Sung (Emirates Journal of Food and Agriculture, 2023)
The objectives of this study were to optimize the medium and culture conditions using a strong γ-aminobutyric acid (GABA) producer as a reference lactic acid bacterial strain, to screen and identify GABA-producing lactic acid bacterial isolates from kimchi, and to determine their extracellular GABA-producing abilities. Thin-layer chromatography was used to screen GABA-producing bacterial isolates and high-performance liquid chromatography was used to evaluate the bacterial GABA production abilities. Species-specific polymerase chain reaction analyses were used to identify GABA-producing bacterial isolates. The optimal medium and culture conditions were found to be the modified Man–Rogosa–Sharpe (MRS) broth (with an initial pH of 6.5) containing 4% sucrose, 5% glutamate, and 1% yeast extract at 37°C for 5 days. After incubation under the optimized culture conditions, 217 kimchi bacterial isolates were screened to evaluate their respective GABA-producing abilities. Screening the 217 kimchi bacterial isolates identified 24 GABA-producing lactic acid bacterial isolates (11%): Lactobacillus plantarum (17), Lactobacillus brevis (six), and Leuconostoc mesenteroides (one), indicating that only a small proportion of the strains produce GABA in the culture broth. The extracellular GABA-producing abilities of the bacterial strains identified in this study varied even within the same species, ranging from 5.8 to 101.7 mM among the 17 GABA-producing L. plantarum isolates and from 8.5 to 88.6 mM among the six GABA-producing L. brevis isolates. In summary, three species of the 24 kimchi GABA-producing bacterial isolates were identified, including one rare species (L. mesenteroides) and the two most dominant species (L. brevis and L. plantarum). Keywords: Lactobacillus brevis; Lactobacillus plantarum; Leuconostoc mesenteroides; Optimization; γ-aminobutyric acid (GABA)